A study on the functional role of the DHCR24 gene in gonadal differentiation and development of Macrobrachium nipponense - Pengfei Cai; Wenyi Zhang; Sufei Jiang; Yiwei Xiong; Hui Qiao; Shubo Jin; Hongtuo Fu (Scientific Reports)
Abstract Sex differentiation in crustaceans is a complex process influenced by various factors, including the androgenic gland and sex-related genes. This study characterized the role of the Mn-DHCR24 gene in the oriental river prawn (Macrobrachium nipponense). We used bioinformatics to analyze sequence features and phylogenetic relationships of a single Mn-DHCR24 gene. The expression patterns of Mn-DHCR24 across different tissues and developmental stages were determined by real-time PCR, and its localization in testis was determined by in situ hybridization. RNA interference was used to knock down Mn-DHCR24 expression, followed by examining changes in sex ratio and gonadal development at the PL10 stage. Additionally, an enzyme-linked immunosorbent assay measured 17α-methyltestosterone levels, and tissue sections were used to characterize gonadal development. The results indicated that Mn-DHCR24 was high expression in testis, which was critical for sperm maturation and gonadal differentiation. RNAi experiments showed the role of Mn-DHCR24 during reproductive regulation rather than as a master gene for sex differentiation. This study further showed that Mn-DHCR24 regulated sex and hormone-related genes, influencing steroid biosynthesis pathways. Together, these findings provided valuable insights into the genetic and hormonal mechanisms of gonadal differentiation in M. nipponense, and supported the development of monosex culture technology.